The effect of milk fat replacement and the addition of Lactobacillus paracasei LPC-37 on the sensory properties of cheeses - Bielecka, Marika (Array, 2020)
The market of ripened cheese is growing rapidly and is highly competitive. Dairy manufacturers have expanded their product range to include cheese-like products where milk fat is replaced with vegetable oils. Cheese-like products have gained popularity among both convenient food producers and consumers looking for cheaper cheese substitutes. Fat determines the sensory attributes of cheeses. The sensory quality of cheese can also be modified through the addition of selected adjunct cultures. This study evaluated the influence of milk fat replacement with palm oil and the addition of an adjunct culture of Lactobacillus paracasei LPC-37 on the sensory attributes of Dutch-type cheeses and cheese-like products during ripening. The chemical composition, content of volatile compounds and colour were analysed. The replacement of milk fat with palm oil contributed to differences in the sensory profile and colour of cheese-like products and deteriorated their sensory quality. However, the addition of L. paracasei LPC-37 improved the sensory characteristics of cheese-like products.